Hypoglossal Nerve Palsy as a Cause of Severe Dysphagia along with the Oropharyngeal Stenosis due to Occipitocervical Kyphosis. (6th March 2019) - Watanabe, Tomohiro; Anno, Masato; Matsubayashi, Yoshitaka; Nagasako, Yuki; Sakuishi, Kaori; Fujimoto, Yoh; Tachibana, Naohiro; Taniguchi, Yuki; Hayashi, Toshihiro; Oshima, Yasushi; Tsuji, Shoji; Tanaka, Sakae
Abstract : Hypoglossal nerve palsy (HNP) is a potential cause of dysphagia. A 66-year-old man presented to our hospital with dysphagia and neck pain. One year prior to his first visit, he had been diagnosed with upper cervical tuberculosis and had undergone posterior C1-2 fixation. The physical examination led to the diagnosis of dysphagia with HNP, and he had severe weight loss. Radiographic examination revealed that the O-C kyphosis had been exacerbated and that the deformity was likely the primary cause of HNP. To restore the swallowing function, O-C fusion surgery was performed. Postoperatively, the patient showed immediate improvement of dysphagia with gradual recovery of hypoglossal nerve function. In the last follow-up evaluation, swallowing function was confirmed with no signs of HNP. Our results indicate that HNP could be more prevalent in cases with severe cervical kyphosis, being underdiagnosed due to the more apparent signs of the oropharyngeal narrowing.